The role of sea buckthorn in skin and mucosal health: a review from an anti-inflammatory perspective - Song, Xiayinan; Sun, Xinyao; Yuan, Huimin; Tang, Yang; Zheng, Fengjie (Frontiers in Pharmacology, 2025)
The skin and mucosal barriers serve as essential frontline defenses, protecting against pathogens, environmental insults, and excessive water loss while maintaining physiological homeostasis. Sea buckthorn (Hippophae rhamnoides), a plant long utilized in traditional medicine, has recently garnered scientific attention for its therapeutic potential in enhancing barrier integrity. Modern studies reveal that its bioactive compounds—including flavonoids, unsaturated fatty acids, vitamins, and carotenoids—exert multifaceted pharmacological effects, such as anti-inflammatory, antioxidant, and tissue-repair properties. These mechanisms not only reinforce barrier function but also mitigate inflammation and accelerate healing. This review synthesizes current evidence on sea buckthorn’s multi-target anti-inflammatory actions and its implications for skin and mucosal health through a unique lens of the inflammatory cascade. By elucidating its molecular and cellular effects across distinct stages of inflammation, we provide a foundation for translating these insights into novel dermatological and mucosal therapeutics. The findings underscore the untapped potential of natural products in barrier protection and regenerative medicine, paving the way for future clinical applications.